Characterisation of permeability to gas of geosynthetic clay liners in unsaturated conditions. Issue 5 (1st October 2010) - Palmeira, E.M.; Mora, H.; Touze-Foltz, N.; Pierson, P.; Mendes, M.J.A.
Abstract : ABSTRACT: This paper is a contribution to the characterisation of permeability to gas of unsaturated GCLs, with applications in cover liners of municipal solid waste landfills. Conducting such tests at low gas pressure gradient limits the risk of moisture distribution change in the bentonite, which has been observed under high pressure gradients. However, a consequence of a low pressure gradient is a small gas flow rate that is difficult to measure with good accuracy. Therefore a solution may be the use of transient state tests, such as the falling pressure test adapted to GCL permeability characterisation. This paper shows the influence of the main parameters related to the test, and to the material tested (natural or activated calcium bentonite, moisture content, presence or not of small cracks in the bentonite). The results obtained showed good repeatability for gas differential pressures up to 40 kPa for the test conditions employed in this work. The results showed that the gravimetric moisture content of the GCL necessary to attain a certain permeability value depends on the nature of the bentonite, which was not observed in terms of volumetric moisture content. However, other factors were shown to be more important than the nature of bentonite in GCL permeability to gas: the desiccation due to the gas flow can significantly increase the permeability, which compromises the GCL's performance as a gas barrier.